Dietary intake of hexabromocyclododecane diastereoisomers (α-, β-, and γ-HBCD) in the Belgian adult population - Goscinny, Séverine; Vandevijvere, Stefanie; Maleki, Mehdi; Overmeire, Ilse Van; Windal, Isabelle; Hanot, Vincent; Blaude, Marie-Noelle; Vleminckx, Christiane; Loco, Joris Van (Chemosphere (Oxford), 2011)
► Medium bound estimated daily intake (EDI) of ΣHBCD was 0.99 ng kg −1 bw d −1. ► Diastereoisomer contribution to the EDI was 67% γ-HBCD, 25% α-HBCD and 8% β-HBCD. ► Food groups contributing the most to EDI: meat and the group of “other” products. ► Levels of HBCD were lower than those found in other EU countries. ► The resulting EDI of ΣHBCD was substantially below the proposed thresholds. A study was performed to assess exposure of the Belgian population to HBCD diastereoisomers. Measurements of HBCD were performed by UPLC-MS/MS, on 45 composite samples from 5 major food groups: dairy (products), meat (products), eggs, fish (products) and a group of “other” products. The medium bound estimated average daily intake (EDI) of ΣHBCD in the Belgian population was 0.99 ng kg −1 bw d −1. The diastereoisomer contribution to the mean EDI showed a predominance of γ-HBCD at 67%, followed by α-HBCD at 25% and 8% for β-HBCD. These results are consistent with the pattern found in the two food groups contributing the most to the EDI: meat (products) and the group of “other” products. Anyway, it has to be noted that diastereomeric distribution of HBCD can change due to bioisomerisation in biological material. Levels of HBCD diastereoisomers found in Belgian food samples of animal origin were low in comparison with those found in other EU countries and the resulting EDI was substantially below the proposed thresholds.